Adaptive Management to Reduce Nest Inundation of a Critically Endangered Freshwater Turtle: Confirming the Win-win. - Espinoza, Tom; Marshall, Sharon M.; Limpus, Duncan J.; Limpus, Col J.; McDougall, Andrew J. (Environmental Management, 2022)
Inundation of Australian freshwater turtle nests has been identified as a threat to recruitment and long-term viability of species such as the critically endangered white-throated snapping turtle (Elseya albagula). Water level fluctuations within water storage infrastructure can inundate significant proportions of E. albagula nests in any year. Using an ecological risk assessment framework, operating rules for a water storage in the Burnett River (South East Queensland, Australia) were implemented to support nesting of E. albagula. Turtles were encouraged to nest at higher elevations on riverbanks by maintaining higher water levels in the impoundment during the nesting season, followed by lowering of water levels during the incubation period to minimise rates of nest inundation from riverine inflows. To verify the success of the new rules, a three-year confirmation monitoring program of nest heights and water levels was undertaken. Results of confirmation monitoring showed that 3% (2018), 11% (2019) and 0% (2020) of E. albagula nests were inundated under the new operating rules, compared to previously estimated nest inundation rates of >20% in ~24% of years of a 118-year simulation period (1890–2008) under previous storage operating rules. Emergency releases from an upstream storage in 2019 and 2020 for dam safety did not affect the success of the rule, demonstrating its resilience to natural and artificial flow regimes. This study demonstrates the importance of confirmation monitoring in verifying the efficacy of targeted changes to water management, and highlights potential application across other water storage infrastructure with threatened freshwater turtle populations requiring adaptive management.